Effect of Egg Albumen, Vegetable Oil, Corn Bran, and Cooking Methods on Quality Characteristics of Chicken Nuggets Using Response Surface Methodology - Pathera, Ashok Kumar (Korean J Food Sci Anim Resour, 2018)
Response surface methodology was used to study the effect of egg albumen (5–15 g), vegetable oil (5–15 g), and corn bran (5–15 g) on sensory and textural (firmness and toughness) quality of chicken nuggets cooked by the oven, steam, and microwave methods. The egg albumen and vegetable oil had a positive linear effect but corn bran had a negative linear effect at p<0.01 on sensory overall acceptability scores of nuggets. Firmness and toughness scores were increased significantly (p<0.01) with the increase in corn bran level in the formulation. The optimum level of egg albumen, vegetable oil, and corn bran were obtained and validated. Cooking methods also affected the sensory and textural quality of nuggets. Steam cooked nuggets had higher values of sensory scores than oven and microwave cooked nuggets. Oven cooked nuggets showed higher values of firmness and toughness than steam and microwave cooked nuggets. Results of this study suggest that emulsion based meat products can be enriched with dietary fiber source like corn bran without compromising the sensory and textural quality of the products.